Uso de LALLS in-line na extrusão de sistemas poliméricos bifásicos - Costa, Lidiane Cristina (Universidade Federal de São Carlos, 2007)
In-line analysis equipments play an important hole in the study of polymer blends extrusion for supplying dynamic information concerning to the morphology of the dispersed phases, such as aspect ratio and size distribution of particles. Among them, the device whose operation is based on light scattering stand out for the versatility, fast data acquisition and for its non destructive operation. Since the morphologic characteristics of the polymer blends affects directly the properties of the material, we presented in this work an improvement of an optical detector based on low angle laser light scattering (LALLS), showing that this equipment is effective in the morphologic characterization of the dispersed phase in diluted polymer dispersions. The studied systems were composed by PS, PA6, Al2O3 and TiO2 embedded in PP matrix. During the extrusion several concentrations of dispersed phase were used in transient state. The LALLS prototype detector developed is effective in the characterization of polymer dispersed phases, based in their light scattering, as well as for ceramic dispersed phases, where the light extinction phenomena are governed by light diffraction. By improving the original acquisition system (hardware and software) and the interpretation of the data, we showed that the prototype is sensitive to the concentrations, particle size distribution and differences in the refraction indexes of the dispersed phase.
Keywords: Extrusão LALLS; Sistema polimérico bifásico; Detector óptico; Tempo real; Luz espalhamento; Luz difração; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA